Odpowiedź :
Odpowiedź:
[tex]a)\ \ (-\frac{1}{2})^3\cdot(-\frac{1}{2})^4\cdot2^7=(-\frac{1}{2})^3\cdot(\frac{1}{2})^4\cdot2^7=-2^{-3}\cdot2^{-4}\cdot2^7=-2^{-3+(-4)+7}=\\\\=-2^{-3-4+7}=-2^{-7+7}=-2^0=-1\\\\\\b)\ \ 0,1^8\cdot0,2^8:0,02^6=(0,1\cdot0,2)^8:0,02^6=0,02^8:0,02^6=0,02^{8-6}=0,02^2=\\\\=0,0004[/tex]
[tex]c)\ \ 0,5^6\cdot(-0,5)^7:0,05^{13}=-0,5^{6+7}:0,05^{13}=-0,5^1^3:0,05^{13}=\\\\=-(0,5:0,05)^{13}=-10^{-13}=-10000000000000\\\\\\d)\ \ \dfrac{44^4}{22^3}=\dfrac{2^4\cdot\not22^4}{\not22^3}=2^4\cdot22^{4-3}=2^4\cdot22^1=2^4\cdot22=16\cdot22=352[/tex]
[tex]e)\ \ \dfrac{64^2\cdot36^2}{6^3\cdot2^7}=\dfrac{(2^6)^2\cdot(6^2)^2}{6^3\cdot2^7}=\dfrac{2^1^2\cdot6^4}{6^3\cdot2^7}=2^{12-7}\cdot6^{4-3}=2^5\cdot6^1=32\cdot6=192\\\\\\f)\ \ \dfrac{4^6\cdot8^6}{32^5}=\dfrac{(4\cdot8)^6}{32^5}=\dfrac{32^6}{32^5}=32^{6-5}=32^1=32[/tex]